Efektifitas Mediasi Non Litigasi Dalam Upaya Penyelesaian Permasalahan Keluarga (Studi Kasus Pada Jamaah Tariqat Naqsabandiyah Babussalam Besilam) - Ade Kurniawan; Abdullah Sani; Diyan Yusri (Peduli Riset dan Pengabdian Masyarakat, 2024)
The problems found in the research location were: Mediation carried out by the people of Babussalam Besilam Village, which was carried out in a non-litigation manner, namely solving household problems by visiting Babussalam Besilam teachers and religious figures who were considered to have knowledge of family jurisprudence so that the mediation process was carried out in a friendly manner and not up to Court. The people of Babussalam Besilam Village carried out mediation by visiting the local Religious Affairs Office, asking for advice and carrying out a mediation process accompanied by BP4 officers, namely a marriage advisory body, as a means for the community to consult about household problems. Based on the problems mentioned above, the researcher proposed research using qualitative research methods through observation, interview and documentation data collection techniques. The results of this research are the effectiveness of problem solving used by mediators in mediating between disputing parties, especially the Tariqat Naqsabandiyah congregation who are experiencing household problems, so one of the effectiveness of the resolution is by taking an approach with the aim of getting results that are acceptable to the parties. who are in conflict, from the case they are facing. The problem solving strategy (Problem Solving) in the mediation carried out in Besilam Village went well and effectively, this was proven by the fact that only one family problem was decided by the court, the rest could be resolved well through non-litigation mediation with traditional leaders and kiyai or caliphs. as the mediator.